Racebook : a personal history of the Internet - Onyebuchi, Tochi (Roxane Gay Books, 2025)
"From the author of Hugo and NAACP Image Award finalist Riot Baby-whose prose has been praised as "magnificent, sharp and whipping" (New York Times)-an original memoir in essays that interrogates how the relationship between race and the Internet has changed in three decades online. When Tochi Onyebuchi realized his acclaimed science fiction and fantasy career had been centrally preoccupied with race, it prompted him to consider his responsibilities as a Black writer in the Internet age. Racebook incisively challenges identity-based presumptions, exploring the early Internet of the late 1990s and early 2000s and recalling in parallel Onyebuchi's origin story as a writer, how his racial presence was defined online then, and how it has shifted in the ensuing years. In brilliantly crafted essays, Onyebuchi also demonstrates the range of his voracious curiosity and razor-sharp wit. From the ever-changing nature of personal writing and free expression to gaming, manga, fandom, and virtual reality-Onyebuchi examines the internet alongside works of literature both classic and new, and asks if our vision for what is possible has really broadened. An utterly original, compelling investigation of race through the lens of the modern Internet age, and a profoundly affecting journey into the heart of community online, Onyebuchi argues for recognizing the individual behind the binary code that shapes our digital lives, ultimately asking "Is this a race book or is it not? Is it either-or? Can it be both-and? Can I?""-- Provided by publisher.